Genetic Counseling Graduate Student Debt: Impact on Program, Career and Life Choices. Issue 5 (1st March 2014) - Kuhl, Ashley; Reiser, Catherine; Eickhoff, Jens; Petty, Elizabeth M.
Abstract: The cost of education is rising, increasing student financial aid and debt for students pursuing higher education. A few studies have assessed the impact of student debt in medicine, physical therapy and social work, but little is known about the impact of student debt on genetic counseling students and graduates. To address this gap in knowledge, a web‐based study of 408 recent alumni of genetic counseling programs in North America was conducted to assess the impact of student debt on program, career and life choices. Over half (63 %; n  = 256/408) of the participants reported that loans were extremely important in their ability to attend their training program, with most using subsidized loans no longer available to current graduate students. While participants were generally satisfied with their genetic counseling education, 83 % ( n  = 282/342) of participants with student debt reported feeling burdened by their debt, which had a median of $40, 000–$50, 000. This debt is relatively close to the median starting salary reported by survey participants ($45, 000–$50, 000), breaching the "20‐10 rule" that states student debt should not exceed 20 % of annual net income. In response to this critical issue, we propose recommendations for the genetic counseling field that may help alleviate student debt impact and burden.